Comparison of anticoagulant effects and safety of argatroban and heparin in healthy subjects - Swan, S K; St Peter, J V; Lambrecht, L J; Hursting, M J (Pharmacotherapy, 2000)
To evaluate and compare the relationship between dosage and coagulation parameters, as well as safety profiles, of ascending bolus and infusion dosages of argatroban versus heparin in three phase I studies. Two randomized, double-blind studies compared argatroban and heparin, and one open-label, dose-escalation study further evaluated argatroban. University teaching hospital clinical research unit. Healthy men (aged 22-62 yrs). In the first study, 36 subjects received an argatroban 30-, 60-, 120-, or 240-microg/kg bolus, or a heparin 30-, 60-, 120-, or 240-U/kg bolus for three subjects, then amended to 15, 30, 60, or 120 U/kg. In the second study, 37 subjects received argatroban 1.25, 2.5, 5, or 10 microg/kg/minute with or without a 250-microg/kg bolus, or heparin 0.15, 0.20, 0.25, or 0.30 U/kg/minute with or without a 125-U/kg bolus. In the third study (open-label), nine subjects received an argatroban 250-microg/kg bolus plus an infusion of 15, 20, 30, and 40 microg/kg/minute. When administered as a bolus dose in the first study, argatroban and heparin both produced dose-related increases in activated clotting time (ACT) and activated partial thromboplastin time (aPTT) within 10 minutes of administration. Dissipation of anticoagulant effect was approximately 4-fold faster for argatroban than for heparin. When administered by infusion with or without a bolus in the second study, argatroban, but not heparin, produced predictable dose-related increases in ACT and aPTT that were generally consistent across both effect measures and modes of administration. Effect steady state was attained by five or more subjects per dosing group receiving argatroban (5-9) but typically two or fewer subjects per group receiving heparin (0-7). Furthermore, upon cessation of infusion, anticoagulant effects dissipated faster for argatroban (effect half-life 18-41 min) than for heparin (effect half-life 23-134 min). When argatroban was infused without a bolus, peak and effect steady-state values for ACT and aPTT generally were attained within 1-3 hours. Data from the second and third studies show that for argatroban dosages up to 40 microg/kg/minute, plasma drug concentrations attained at 4 hours of infusion increased linearly with dose, and weight-adjusted plasma clearance was dose independent. In all studies, argatroban and heparin were well tolerated. Anticoagulation was more predictable with argatroban than with heparin as measured by ACT and aPTT, with comparable safety profiles.